Belief revision and relevance - Falappa, Marcelo Alejandro (1999)
The aim of this work is to relate two apparently independent concepts as belief revision and relevance. We propose a formal characterization for the notion of (ir)relevance by means of a set of postulates. Then we define (ir)relevance using change operators and we show that the contraction operations of the AGM model can be modeled through (ir)relevance relations and vice versa.